Rapid Aid Education For Burns Through The Hospital Health Program Of The Surgical Polyclinic Of Rsud Haji Surabaya - Adinda Widita; Ahmad Hanif Muwaffaq; Kanina Alma Dystanti; Shela Prilia Pratama; Amalia Rahma Maulida; Ulfiyah Labibah Muharromi Kharisma Putri (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2026)
Background: Burns are a global public health problem with high morbidity and mortality, so rapid and appropriate first aid is crucial to prevent complications and improve patients' quality of life. However, many people still take incorrect initial steps, necessitating hospital-based health education to increase public knowledge and awareness. Objective: Increase patient, family and community knowledge about the correct first aid steps for burns and reduce the number of complications due to incorrect initial treatment of burns. Methods: This study used the Service Learning method with a pre-test and post-test design to assess the effectiveness of the outreach program. The activity was conducted in the waiting room of the Surgical Polyclinic at Haji Hospital, Surabaya, and was attended by 30 respondents. The educational intervention included delivering material using PowerPoint presentations, leaflets, and posters, as well as interactive discussion sessions and quizzes. Data were collected through pre-test and post-test questionnaires to measure the increase in respondents' knowledge. Analysis was conducted by comparing the average scores before and after the intervention to assess significant increases in knowledge. Results: On the pretest, most participants achieved only low to moderate scores, with the highest distribution at 40 (26.7%) and 30 (20%). In contrast, on the posttest, most participants achieved high scores, with 43.3% achieving a perfect score (100) and 30% achieving a score of 90.